A novel atmospheric freeze dryer using simultaneous application of subzero and hot air streams using a vortex chiller. Issue 12 (9th September 2016) - Rahman, S. M. A.; Saidur, R.
ABSTRACT: The objective of this research was to develop an atmospheric freeze-drying (AFD) system for heat-sensitive materials. A laboratory scale AFD system consisting of a vortex chiller was designed and fabricated. A vortex tube was used to convert compressed air into a subzero and a hot air stream. The system used the simultaneous application of subzero air stream and hot air carrier gas coupled with radiant heat input for drying heat-sensitive materials. A parametric evaluation of this drying system was performed. Comparison of drying characteristics and the physical quality (e.g., color, shape, size) with vacuum freeze and traditional AFD was also performed. Results revealed that the proposed system is a suitable and viable alternative without compromising the quality compared to traditional freeze-drying system.